The effect of a booster dose of HPV tetravalent vaccine after 51 months: implications for extended vaccination schedules - Eduardo Lazcano-Ponce; Martha Carnalla-Cortés; Tonatiuh Barrientos-Gutierrez; Leticia Torres-Ibarra; Aurelio Cruz-Valdez; Jorge Salmerón; Mauricio Hernández-Avila (Salud Pública de México, 2018)
Objective. To asses the non-inferiority between two different vaccination schedules one month after the administration of the third dose. Materials and methods. Evaluated the anti-HPV 16/18 antibody titers induced by quadrivalent HPV vaccine administered using two different schedules in girls 9 to 10-year-old girls: a traditional (0-2-6) and an alternative (0-6-50). Blood samples were collected at month 7, 21 and 51. Results. The antibody geometric mean titer ratios one month after the application of the third dose –month 51 for the alternative and month 7 for the traditional– were 1.55 for HPV16 (95%CI, 1.15-2.08) and 1.53 for HPV18 (95%CI, 1.12- 2.09). The seropositive rate was above 99% in both groups. Conclusions. The application of an alternative 3-dose schedule in 9 to 10-year-old girls induces a non-inferior immune response compared to the standard one month after the last dose. Further research is needed to understand the minimal number of doses and their timing to provide the best coverage for HPV infection.